The Arctic Soil Bacterial Communities in the Vicinity of a Little Auk Colony - Zielińska, Sylwia; Kidawa, Dorota; Stempniewicz, Lech; Łoś, Marcin; Łoś, Joanna M. (Frontiers in Microbiology, 2016)
Due to deposition of birds’ guano, eggshells or feathers, the vicinity of a large seabirds’ breeding colony is expected to have a substantial impact on the soil’s physicochemical features as well as on diversity of vegetation and the soil invertebrates. Consequently, due to changing physicochemical features the structure of bacterial communities might fluctuate in different soil environments. The aim of this study was to investigate the bacterial assemblages in the Arctic soil within the area of a birds’ colony and in a control sample from a topographically similar location but situated away from the colony’s impact area. A high number of OTUs found in both areas indicates a highly complex microbial populations structure. The most abundant phyla in both of the tested samples were: Proteobacteria, Acidobacteria, Actinobacteria and Chloroflexi, with different proportions in the total share. Despite differences in the physicochemical soil characteristics, the soil microbial community structures at the phylum level were similar to some extent in the two samples. The only share that was significantly higher in the control area when compared to the sample obtained within the birds’ colony, belonged to the Actinobacteria phylum. Moreover, when analyzing the class level for each phylum, several differences between the samples were observed. Furthermore, lower proportions of Proteobacteria and Acidobacteria were observed in the soil sample under the influence of the bird’s colony, which most probably could be linked to higher nitrogen concentrations in that sample.